The Open- Fracture Patient Evaluation Nationwide (OPEN) study. (2022) - Hadfield, J. N.; Omogbehin, T. S.; Brookes, C.; Walker, R.; Trompeter, A.; Bretherton, C. P.; Gray, A.; Eardley, W. G. P.
No abstract available